Pengaruh Koneksi Politik pada Hubungan Antara Kepemilikan Manajerial dan Kepemilikan Institusional dengan Konservatisme Akuntansi: Studi Empiris Perusahaan Sektor Energi yang Tercatat di BEI Periode 2021-2023 - Hermawan Rizky Wibowo; Eny Kusumawati (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Conservatism is prudent financial reporting that shows careful consideration and response to future uncertainties. This study analyzes the effect of political connections on the relationship between managerial ownership and institutional ownership with accounting conservatism in energy sector companies listed on the Indonesia Stock Exchange for the period 2021-2023. The sampling technique used in this study was purposive sampling.  A total of 117 companies have met the criteria as observation units. The analysis method used is multiple linear regression analysis. The results of the study provide empirical evidence that the managerial ownership variable affects accounting conservatism. Meanwhile, the institutional ownership variable has no effect on accounting conservatism. Then in this study also states that the moderation variable of political connection is not able to moderate the relationship between managerial ownership and institutional ownership with accounting conservatism.